Parental problems in early children's education in the digital era - Navy Ana Saputri; Hayani Wulandari (Inovasi Kurikulum, 2024)
This research explores the challenges and parenting patterns in early childhood education in the digital era. With rapid technological advancements, parents play a crucial role in guiding their children through new dynamics. The literature review highlights the importance of a balanced parental approach, providing attention and affection while adapting to technological advancements. Employing a quantitative approach with a cross-sectional design, the study investigates parental issues and technology's impact on early childhood development. Data on technology use, screen time limits, allowed content types, and parental educational strategies were collected and statistically analyzed through a structured questionnaire. The research findings reflect diverse parental views on technology use, with the majority acknowledging its benefits but expressing concerns about potential negative impacts. The conclusion underscores the significance of active collaboration between parents, educators, and the community to create a balanced educational environment in the digital era. The proposed solution involves enhancing parental understanding and fostering intensive collaboration to develop a holistic approach to technology use in early childhood education.   Abstrak Penelitian ini bertujuan untuk menggali permasalahan dan pola pengasuhan orangtua dalam pendidikan anak usia dini di era digital. Dengan pertumbuhan teknologi yang pesat, peran orangtua dalam membimbing anak-anak mereka menghadapi dinamika baru. Tinjauan literatur menyoroti pentingnya pendekatan orangtua yang seimbang dalam memberikan perhatian dan kasih sayang, sambil menyesuaikan diri dengan kemajuan teknologi. Penelitian ini mengadopsi pendekatan kuantitatif dengan desain lintas-seksi untuk mengeksplorasi masalah orang tua dan dampak penggunaan teknologi pada perkembangan anak usia dini. Melalui penggunaan kuesioner terstruktur, data terkait penggunaan teknologi, batasan waktu layar, jenis konten yang diperbolehkan, dan strategi pendidikan orangtua dikumpulkan dan dianalisis secara statistik. Hasil penelitian mencerminkan keragaman pandangan orangtua tentang penggunaan teknologi, dengan sebagian besar mengakui manfaatnya tetapi juga mengekspresikan kekhawatiran terhadap dampak negatifnya. Kesimpulan menyoroti pentingnya kolaborasi aktif antara orangtua, pendidik, dan masyarakat untuk menciptakan lingkungan pendidikan yang seimbang di era digital, dengan solusi yang melibatkan pemahaman yang lebih baik oleh orangtua dan kerja sama intensif untuk menciptakan pendekatan holistik terhadap penggunaan teknologi dalam pendidikan anak usia dini. Keywords: Era digital; gawai; pola pengasuhan